2020
DOI: 10.1017/s0001972019000950
|View full text |Cite
|
Sign up to set email alerts
|

Global health's durable dreams: ethnography, ‘community health workers’ and health without health infrastructure

Abstract: Tracing the persistence of community health workers (CHWs) as a key category in both global health policy and anthropological representation, this article asks how enduring scholarly investments in CHWs can reveal changing political stakes for both health work and ethnographic research. Amid renewed calls for a focus on health systems and universal health coverage, the article suggests that the durability of attention to CHWs is instructive. It simultaneously points to the imbrication of health with political … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Also highly coveted were monthly incentives given to peer educators charged with reaching MSM to count and refer them to HIV testing. Across global health discourse and monitoring and evaluation documents, peer educators, as one iteration of a vast global network of “community health workers” (McKay 2020), are idealized as selfless volunteers dedicated to their community. NGO staff members, too, internalize logics that valorize unpaid altruistic volunteerism: on one occasion, a “troublesome” peer educator named Fatsani, who rarely met his monthly quotas of “MSM reached,” was accused of “poisoning” the other peer educators working in his district by “making their passion into a commercial endeavor.” In this rendering, Fatsani's refusal to “work”—and his repeated complaints about inadequate payment—taint dominant discursive renderings of peer education as selfless, voluntary, and driven by passion for community.…”
Section: Yielding Positives: Labor Capturementioning
confidence: 99%
“…Also highly coveted were monthly incentives given to peer educators charged with reaching MSM to count and refer them to HIV testing. Across global health discourse and monitoring and evaluation documents, peer educators, as one iteration of a vast global network of “community health workers” (McKay 2020), are idealized as selfless volunteers dedicated to their community. NGO staff members, too, internalize logics that valorize unpaid altruistic volunteerism: on one occasion, a “troublesome” peer educator named Fatsani, who rarely met his monthly quotas of “MSM reached,” was accused of “poisoning” the other peer educators working in his district by “making their passion into a commercial endeavor.” In this rendering, Fatsani's refusal to “work”—and his repeated complaints about inadequate payment—taint dominant discursive renderings of peer education as selfless, voluntary, and driven by passion for community.…”
Section: Yielding Positives: Labor Capturementioning
confidence: 99%
“…Conclusively, the Nigeria's Federal Ministry of health found that Nigerian"s health system is filled with high level of corruption and fraud; ineffective coordination among the three levels of government; the attitude of health workers towards patients; poor health service delivery; inadequate public and private health funding; poor working environment, limited opportunities for continuing education, massive migration of health workers to greener pastures; poor implementation of guidelines, few training opportunities; poor skills for supplychain management among providers; poor location of healthcare centers; poor utilization of research findings; lack of effective leadership for the successful implementation of health promotion and community participation in PHC [6]. According to the World Health Organization, PHC could only achieve its goals, be more responsive and accountable to societal needs through the appointment of good leaders to coordinate primary health care services.…”
Section: The Participant Discussed Further That "It Is Like You Don't...mentioning
confidence: 99%
“…According to a study conducted in Nigeria showed that most Federal and State hospitals are built in the city; so nearly all the health workers want to work in the city because of their remuneration, infrastructure, other opportunities, and benefits [6]. These opportunities make most of the competent health care professionals to be working and even some are still struggling to work with the Federal and State hospitals in the cities, leaving the grass root health centres (local government hospitals) with no choice health workers [7].…”
Section: Introductionmentioning
confidence: 99%